Comparative Readability Analysis of Online Patient Education Resources on Inflammatory Bowel Diseases - Rishabh Gulati; Mohammad Nawaz; Linh Lam; Nikolaos T. Pyrsopoulos (Canadian Journal of Gastroenterology and Hepatology)
Background. The National Institutes of Health recommend a readability grade level of less than 7th grade for patient directed information. In this study, we use validated readability metrics to analyze patient information from prominent websites pertaining to ulcerative colitis and Crohn’s disease. Methods. The terms “Crohn’s Disease,” “Ulcerative Colitis,” and “Inflammatory Bowel Disease” were queried on Google and Bing. Websites containing patient education material were saved as a text file and then modified through expungement of medical terminology that was described within the text. Modified text was then divided into subsections that were analyzed using six validated readability scales. Results. None of the websites analyzed in this study achieved an estimated reading grade level below the recommended 7th grade. The median readability grade level (after modification) was 11.5 grade levels for both Crohn’s disease and ulcerative colitis. The treatment subsection required the highest level of education with a median readability grade of 12th grade (range of 6.9 to 17). Conclusion. Readability of online patient education material from the analyzed popular websites far exceeds the recommended level of being less than 7th grade. Patient education resources should be revised to achieve wider health literacy.